Spatial analysis of leptospirosis and toxoplasmosis seroprevalence in the canine population in an area of socioeconomic and environmental vulnerability - Belaz, L. D. [UNESP]; Santana, C. F.S. [UNESP]; Victória, C. [UNESP]; Pantoja, J. C.F. [UNESP]; Freitas, J. C.; Navarro, I. T.; Pereira, M. R. [UNESP]; Arabe Filho, M. F. [UNESP]; Oliveira, L. M.; Paes, A. C. [UNESP]; Ribeiro, M. G. [UNESP]; Megid, J. [UNESP] (FapUNIFESP (SciELO), 2023)
Leptospirosis and toxoplasmosis are zoonoses of occupational character that are spread worldwide, mainly in tropical and socioeconomically vulnerable areas. Both diseases have vertebrate hosts, which spread the infectious agent to the environment and are potentially infectious to humans and can progress to fatal cases. The present study reinforces the importance of One Health for the control and prophylaxis of leptospirosis and toxoplasmosis using sentinel animals in areas of socioeconomic vulnerability based on a serological study. A total of 336 blood samples were obtained from the canine population of the urban district, which has high rates of poverty and sanitation. The results were analyzed based on seroreactivity animals and georeferencing by kernel spatial mapping. A total of 43.3% (52/120) of the animals were seroreagents for anti-Leptospira spp., with a predominance of Canicola (35/52 = 67.3%) and Pyrogenes (5/52 = 9.6%), while 52.97% (178/336) of the dogs were seroreactive for anti-Toxoplasma gondii. The presence of seroreagent dogs for both zoonosis alert to the inadequate hygienic-sanitary conditions of the studied region, and highlight the importance of a survey of the social, economic and environmental structure to identify factors related to the links in the epidemiological chain of pathogen transmission and necessary corrective actions.
Análise espacial da soroprevalência de leptospirose e toxoplasmose no população canina em área de vulnerabilidade socioeconômica e ambiental
Keywords: Leptospirosis; single health; Toxoplasma gondii; vulnerable population; Zoonoses